Profiling in wildlife crime: Recovery of human DNA deposited outside. (July 2018) - Mcleish, K.; Ferguson, S.; Gannicliffe, C.; Campbell, S.; Thomson, P.I.T.; Webster, L.M.I.
Highlights: Scoping experiments were run to assess the persistence of human touch-DNA outside. From traps, full DNA profiles could be recovered after at least 10 days. From carcasses, human DNA profiles could be recovered after at least 1 day. DNA profiling should be attempted on illegally set traps. DNA profiling should be attempted on fresh carcasses in wildlife crimes. Abstract: Incidents of bird of prey persecution receive a lot of media coverage in the UK, with investigations rarely recovering sufficient evidence to proceed to prosecution. One of the main challenges is to identify a suspect, as these offences are carried out in remote locations without witnesses, and crime scenes may not be found for days. However, traps, poisoned baits and bird of prey carcasses can be recovered from these crime scenes. This study aimed to determine whether reportable human DNA profiles could be recovered from any of these substrates after periods of time outside. Experiments depositing human touch DNA on duplicate substrates (traps, rabbit baits and corvid carcasses) set for 0, 1, 2, 4, 7 and 10 days outside were carried out, with DNA recovery and profiling following standard operating procedures for Scottish Police Authority Forensic Services. Weather conditions varied among experiments, including some heavy rainfall. Results demonstrated that it was possible to obtain reportable DNA profiles from all substrates after at least 1 day outside. Most promisingly, the traps showed no drop-off in DNA persistence over the experiments as complete DNA profiles were obtained after the full 10 days outside. A further experiment using 4 bird of prey carcasses confirmed that it is possible to obtain reportable human DNA profiles from them after 1 day outside (n = 2 reportable profiles). These results show that touch DNA can persist in an outdoor environment, and provide a tantalising avenue for inquiry in bird of prey persecution investigations.